A qualitative comparative analysis of neighborhood recovery following Hurricane Katrina. Issue 4 (4th November 2014) - Jordan, Elizabeth; Javernick-Will, Amy; Amadei, Bernard
Abstract : Purpose: – The purpose of this research is to examine why communities facing the same disaster recover differentially and determine pathways to successful disaster recovery in the research setting of New Orleans neighborhoods affected by Hurricane Katrina. While previous studies suggest that there are a variety of pathways to recovery, a broader cross-case comparison is necessary to generalize these pathways into a recovery framework. Specifically, this study seeks to determine what pre-disaster and post-disaster causal factors, alone or in combination, were important to recovery following Hurricane Katrina. Design/methodology/approach: – This paper presents a cross-case comparative study of neighborhood-level recovery. Based on prior work, which used the Delphi method to determine hypothesized causal factors and indicators of recovery, data was collected through publically available sources, including the US Census, the Greater New Orleans Community Data Center and previously completed studies for 18 damaged neighborhoods. Fuzzy-set qualitative comparative analysis was used due to its ability to analyze both quantitative and qualitative data for smaller case studies. Findings: – The results show that there are multiple pathways combining pre-disaster community factors and post-disaster actions that led to recovery, as measured by population return. For example, economic capacity is nearly sufficient for recovery, but a combination of low social vulnerability, post-disaster community participation, a high proportion of pre-World War II housing stock and high amounts of post-disaster funds also led to recovery. Originality/value: – This research uses a novel method to link pre-disaster measures of resilience and vulnerability to recovery outcomes and, through cross-case comparison, generates results that will enable researchers to develop a theory of sustainable community recovery.